Evaluation on Quranic language textbook for beginners (LQM0813): teachers’ and students’ perspectives - Md Azmi, Afiqah; Idris, Nor Ashikin; Arshad, Mastura; Mustapai, Mohd Zulhisyam; Ab Jabbar, Muhammad Bahari; Md Zain, Zairul (2022)
Textbook is the main tool and reference for the teaching and learning process in classroom. This research investigates the new Quranic Language textbook designed for the beginners (LQM0813) that contains four elements, which are language skills (reading, listening, writing and speaking), grammar, Sejahtera Academic Framework (SAF) and Common European Framework of Reference (CEFR). The purpose of this research is to evaluate the teachers’ and students’ perspectives towards this textbook and determine the pedagogical methods and suitability of the book towards students’ needs. 31 Quranic Language Department (QLD) teachers and 275 students are selected, and data are collected from the online survey through Google Form. The questionnaire consists of 57 items for both teacher’s and student’s version. The result shows that this textbook satisfies the students’ needs especially in encouraging them to participate in interactive activities and group discussions, besides enhancing their four language skills to understand Arabic language. From the teachers’ perspectives, the contents of this textbook improve students’ abilities in learning Arabic language, especially in pronouncing Arabic alphabets correctly, differentiating between ال قمرية and ال شمسية, identifying basic Masculine and Feminine nouns, and mentioning pillars of the prayer in Arabic. Keywords. Evaluation, Quranic Language textbook, language skills, Sejahtera Academic Framework (SAF)